2014
DOI: 10.5888/pcd11.140211
|View full text |Cite
|
Sign up to set email alerts
|

Building an Evidence Base for the Co-Occurrence of Chronic Disease and Psychiatric Distress and Impairment

Abstract: IntroductionMental disorders and chronic diseases have been reported to independently affect half of the US population. The objective of this study was to evaluate the comorbid nature of these conditions.MethodsWe analyzed data from 39,954 participants from the 2009 California Health Interview Survey who reported both psychological distress and impairment, on the basis of the Kessler 6 and the Sheehan Disability Scale, and 1 or more of 4 chronic diseases (type 2 diabetes, high blood pressure, asthma, heart dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Several studies have shown an association between depression and hypertension [6][7][8][9][10][11][12][13][14], although others have found no such association [15,16], or an association with a generally increased disease burden [17]. Most of these studies have been made by recording the occasional blood pressure and/or intake of antihypertensive drugs, or selfreported hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an association between depression and hypertension [6][7][8][9][10][11][12][13][14], although others have found no such association [15,16], or an association with a generally increased disease burden [17]. Most of these studies have been made by recording the occasional blood pressure and/or intake of antihypertensive drugs, or selfreported hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, medical comorbidities, HIV and current STI, were significantly associated with high K-10 scores among male detainees in labour camps. The relationship between medical comorbidity and its association with psychological distress has been reported elsewhere (Byles et al, 2014;Li et al, 2009;Piane & Smith, 2014;Strine et al, 2006). Other factors, such as poorer health care in the labour camps, may be a contributing factor among male detainees experiencing high psychological distress.…”
Section: Discussionmentioning
confidence: 86%
“… 66 Its three items are complemented by a fourth dimension to which the patient records the levels of stress in the same visual analog scale as above three items. 67 …”
Section: Methodsmentioning
confidence: 99%